2022
DOI: 10.3390/ijms23042031
|View full text |Cite
|
Sign up to set email alerts
|

Chicoric Acid Prevents Neuroinflammation and Neurodegeneration in a Mouse Parkinson’s Disease Model: Immune Response and Transcriptome Profile of the Spleen and Colon

Abstract: Chicoric acid (CA), a polyphenolic acid compound extracted from chicory and echinacea, possesses antiviral, antioxidative and anti-inflammatory activities. Growing evidence supports the pivotal roles of brain–spleen and brain–gut axes in neurodegenerative diseases, including Parkinson’s disease (PD), and the immune response of the spleen and colon is always the active participant in the pathogenesis and development of PD. In this study, we observe that CA prevented dopaminergic neuronal lesions, motor deficits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In addition, a recent study showed that CA reverses the levels of interleukin-17 (IL-17) and transforming growth factor-β (TGF-β) in mice. The potential targets and mechanisms of CA regulating spleen and intestinal immune response were elucidated by analyzing the expression of differential genes using transcriptomics . This suggests that we can further explore the molecular mechanism and key targets of CA in alleviating colitis from the perspective of immunity in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study showed that CA reverses the levels of interleukin-17 (IL-17) and transforming growth factor-β (TGF-β) in mice. The potential targets and mechanisms of CA regulating spleen and intestinal immune response were elucidated by analyzing the expression of differential genes using transcriptomics . This suggests that we can further explore the molecular mechanism and key targets of CA in alleviating colitis from the perspective of immunity in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Velíšek (2006) stated that Echinacea extract counteracted dopamine, acetylcholine, opioids, and the GABAergic system in the brain; interestingly, Konishi et al (2005) and Woelkart et al (2009) attributed this effect to the active components inside the extract such as cafeic acid, rosmarinic acid, and alkamide that can easily pass through the blood-brain barrier and exert their protective effect. Also, the study of Wang et al (2022) indicated that chicoric acid can prevent dopaminergic lesions, motor de cits and glial activation in mice with Parkinson disease, and increase neurotrophic factor, dopamine, and serotonin levels in brain striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Non-transgenic male mice were used as the wild-type (WT) mice, in parallel with only the male 5xFAD mice. The mice were assigned to four groups ( n = 10/group): the intragastrically injected WT (phosphate buffer solution (PBS)) group, the 5xFAD (PBS) group, the 5xFAD + CA group (40 mg/kg) group, and the WT + CA (40 mg/kg) group [ 11 ]. The CA dose of 40 mg/kg was chosen based on previous studies which showed that CA induces a therapeutic effect, and that there is no toxicity at this dose.…”
Section: Methodsmentioning
confidence: 99%
“…It has exhibited extensive pharmacological effects, such as regulating glycolipid metabolism and reducing inflammation, oxidation and aging [ 10 ]. It was shown that CA prevented dopaminergic neuropathy, motor deficit and glial activation in N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease (PD) in mice [ 11 ]. CA has also displayed neuroprotective effects in a mouse model of PD via modulation of the gut microbiota and TLR-4 signaling pathway [ 12 ].…”
Section: Introductionmentioning
confidence: 99%